2017
DOI: 10.2147/opth.s130706
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of intense pulsed light and meibomian gland expression efficacy on relieving signs and symptoms of dry eye disease due to meibomian gland dysfunction

Abstract: PurposeThe aim of this study was to estimate the efficacy of intense pulsed light (IPL), followed by meibomian gland expression (MGX), for reducing the number and severity of signs and symptoms of dry eye disease (DED) secondary to meibomian gland dysfunction (MGD).Patients and methodsIn a prospective study conducted in two sites, 40 subjects (80 eyes) with moderate to severe MGD were enrolled. Major inclusion criteria consisted of at least two of the following measures being compatible with DED in both eyes: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
115
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(140 citation statements)
references
References 33 publications
11
115
1
Order By: Relevance
“…More than a decade ago, Toyos et al noticed that facial skin rosacea patients treated with IPL reported a significant improvement in their dry eye symptoms 17. Since then, a number of studies confirmed that IPL therapy reduces both signs and symptoms of dry eye 1823. In these studies, IPL therapy comprised several sessions given several weeks apart.…”
Section: Introductionmentioning
confidence: 99%
“…More than a decade ago, Toyos et al noticed that facial skin rosacea patients treated with IPL reported a significant improvement in their dry eye symptoms 17. Since then, a number of studies confirmed that IPL therapy reduces both signs and symptoms of dry eye 1823. In these studies, IPL therapy comprised several sessions given several weeks apart.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, it has begun to be incorporated into dermatological practice for the treatment of rosacea, telangiectasia, acne, and other skin conditions. Its application improved in the following years, being proposed in 2002 possible bene its in ophthalmic diseases [3][4][5]. Ophthalmologist Rolando Toyos was the irst to suggest the use of IPL for the treatment of MGD, from the observation of objective and subjective improvement of DES symptoms in patients with periocular rosacea undergoing Pulsed Light therapy [8][9][10].…”
Section: Ipl Therapymentioning
confidence: 99%
“…Historically, aqueous de iciency has represented for ophthalmology, the primary pathophysiological substrate in the genesis of the syndrome. However, new studies show that 80% of patients have evaporative or mixed-type dysfunction mechanisms [1,5]. Meibomian gland dysfunction (MGD) is the primary cause of evaporative dry eye and contributes to the development of the aqueous subtype.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations